Discretion of local government spending in sinaloa: strength or weakness? (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2015)
The degree of equity generated by the amount of resources exercised by way of rustic property tax (IPR) in receiverships the municipality of Guasave in the period 2008 to 2010. The study was conducted with non-experimental, descriptive method with a mixed approach was analyzed; its population was delimited at 12 receiverships the municipality. It shows that the government of the municipality of Guasave distributes resources Rustic property tax on a discretionary basis, benefiting receiverships and harming other major work to funnel money into better public services and implement them. The requirement of society is that public policies designed to impact fairly and equitably among communities that comprise it. The results call for the implementation of public policies conducive to raise social welfare indicators among its inhabitants with a fair distribution of resources, which results in designing a formula that involves distributional factors for its effectiveness, such as: number population by receivership, number of locations, land area, collection efficiency, among others.
Keywords: fairness; property tax; public policy; welfare